CHANGES IN SKIN MICROCIRCULATION ON THE ANTERIOR ABDOMINAL WALL OF PATIENTS WITH ACUTE SURGICAL PATHOLOGY - Валиахмедова, Кристина Валерьевна; Алексеев, Андрей Михайлович; Баранов, Андрей Игоревич; Кемеров, Сергей Викторович; Блинова, Наталья Павловна (Medicine in Kuzbass, 2019)
Objective. Assessment of perfusion changes in a tissue of the wound area in patients with acute surgical pathology.Methods. Clinical experience made up of 60 patients with acute surgical diseases, and 30 healthy volunteers.Results. In the main group the healing was by primary intention, the average index of microcirculation on the first day was 12.8 ± 1,5 units building, on the third day of 10,7 ± 1,2 units building, on the fifth day 7,5 ± 1,2 floor units, throughout the postoperative period, the average was 10.3 ± 1,4 per. units, which corresponds to a hyperemic hemodynamic type of microcirculation. No statistically significant differences in the nine regions of the anterior abdominal wall were revealed in the comparison group. The perfusion indices made up from 3.8 to 6.5 micro-units, an average of 4.7 ±1,2 building units, which corresponds to normocalcaemia hemodynamic type of microcirculation.Conclusions. During the analysis with the help of laser Doppler fluometry revealed that in the early postoperative period in the wound there is a change in perfusion as a result of traumatic injury of arterioles and venules, inflammatory reaction, which is confirmed by an increase in microcirculation by 54.4 %.
Keywords: acute surgical pathology; microcirculation; perfusion